Enhanced Oil Recovery using Smart Water Injection (Journal of Engineering, 2018)
Smart water flooding (low salinity water flooding) was mainly invested in a sandstone reservoir. The main reasons for using low salinity water flooding are; to improve oil recovery and to give a support for the reservoir pressure.In this study, two core plugs of sandstone were used with different permeability from south of Iraq to explain the effect of water injection with different ions concentration on the oil recovery. Water types that have been used are formation water, seawater, modified low salinity water, and deionized water.The effects of water salinity, the flow rate of water injected, and the permeability of core plugs have been studied in order to summarize the best conditions of low salinity water flooding. The result of this experimental work shows that the water without any free ions (deionized water) and modified low salinity water have improved better oil recovery than the formation water and seawater as a secondary oil process. The increase in oil recovery factor related to the wettability alteration during low salinity water flooding which causes a decrease in the interfacial tension between the crude oil in porous media and the surface of reservoir rocks. As well as the dissolution of minerals such as calcite Ca+2 was observed in this work, which causes an increase in the pH value. All these factors led to change the wettability of rock to be more water-wet, so the oil recovery can be increased.